High aperture efficient slot antenna surrounded by the cavity and narrow corrugations at Ka‐band and Ku‐band. Issue 12 (26th June 2018) - Alkaraki, Shaker; Gao, Yue; Parini, Clive
Abstract : A design criterion for a small, compact, high‐aperture‐efficient antenna is proposed in this study. The proposed criterion is validated experimentally through fabricating and testing two prototypes for Ku‐band and Ka‐band applications. The proposed antenna design consists of a resonance slot perforated in an aluminium plate and surrounded by a cavity and two corrugations. The proposed Ku‐band antenna has an aperture efficiency of 74.3% and a measured gain of 12.2 dBi at 13 GHz, while the Ka‐band antenna resonates at 28.5 GHz with a peak aperture efficiency of 78% and a gain of 12.9 dBi. The gain of both antennas is dramatically boosted by the radiation from the cavity and corrugations, resulting in a significant enhancement in the aperture efficiency.